810 How much does it really cost? Barriers, Bottlenecks and Billing in Sleep Diagnostics. (3rd May 2021) - Jambulingam, Nikita; Stretch, Robert; Butz, David; Zeidler, Michelle
Abstract: Introduction: Utilization rates of home sleep apnea tests (HSATs) versus in-lab polysomnograms (PSGs) vary greatly among healthcare institutions. HSATs can provide expanded testing capacity and offload operational bottlenecks in sleep labs, however, the financial benefit of this is not well quantified. Comparison of testing utilization and profitability between institutions can provide greater insight into decisions regarding sleep lab operations and expansion. Methods: We analyzed profitability of HSATs and PSGs in 2018–2019 at two separate institutions with vastly different operational constraints and healthcare delivery models: Greater Los Angeles VA Healthcare System (GLA-VAHS) and University of California Los Angeles Health System (UCLA-HS). Both institutions own and operate independent sleep labs and offer HSATs for the diagnosis of sleep apnea. Profitability was calculated using contribution margin (CM) which factors out high fixed costs of healthcare infrastructure. CM was calculated by subtracting variable direct costs from revenue. Results: The non-diagnostic HSAT rate was higher at GLA-VAHS compared to UCLA-HS (30.5% versus 13.1%). At both GLA-VAHS and UCLA-HS, HSATs were more profitable than PSGs on a per-unit basis (CM 47% for HSATs and 29% for PSGs at GLA-VAHS vs. 78% and 66% at UCLA-HS, respectively). Comparing the two institutions, PSGs were 14.8 times more profitable and HSATs were two times more profitable at UCLA-HS versus GLA-VAHS. When analyzed on a per-day basis, HSATs were more profitable at GLA-VAHS but PSGs were more profitable at UCLA-HS. Conclusion: Reimbursement rates significantly impact institutional decisions to expand utilization of HSATs versus PSGs. Due to higher per-unit reimbursement rates, non-governmental and larger academic institutions may opt to aggressively expand sleep lab capacity. However, risks and benefits of such a strategy should be taken into account in light of changing market patterns and declining reimbursement rates for PSGs. Despite the seemingly higher profitability at the current time, future market volatility in PSG profitability may cause delayed amortization of costs for PSGs at large academic and private institutions compared to the relatively lower cost of expanding HSAT capacity. It may be beneficial for all types of institutions, regardless of current reimbursement rates, to expand HSAT capacity concomitantly with sleep lab expansion to mitigate financial risk. Support (if any):